Physicochemical characterization of milk fermented by Lactobacillus helveticus added with hibiscus extract during storage (Research, Society and Development, 2022)
This work proposed to develop a milk fermented by Lactobacillus helveticus (LH) or associated with a culture of Streptococcus thermophilus (LHST) added with hibiscus extract and to evaluate the antioxidant activity and growth evolution of lactic cultures during storage under refrigeration at 4 ± 1ºC. Fermented milk received free form hibiscus extract (LHExL and LHSTExL) or encapsulated with PVP and Tween 80 (LHExE and LHSTexE). Antioxidant activity (DPPH and FRAP) was evaluated at 1, 15 and 30 days. The results showed that the titratable acidity content was lower after fermentation. The viability of the lactic acid bacteria was satisfactory, which met the legal requirements and remained stable up to 30 days of storage for both fermented milk (LH and LHST). The antioxidant activity against the DPPH radical was greater than 80%, but it did not show conclusive results regarding the interaction of lactic cultures and the different forms of application of the hibiscus extract. However, LH showed greater antioxidant activity by the FRAP method when associated with hibiscus extract encapsulated in the initial time. This analysis allowed to observe that the association of hibiscus extract regardless of the form conveyed to fermented milk increased the antioxidant activity by the FRAP method and this remained stable over the storage time. Therefore, the study allowed to conclude that the fermented milk associated with the hibiscus extract contributed to the increase in antioxidant activity and remained stable over the storage time.